Pelatihan Dan Pendampingan Pembuatan Promosi Media Sosial Bagi Usaha Kerajinan Tenun Ikat Tradisional Di Desa Semarapura Tengah Kabupaten Klungkung - Ni Nyoman Kerti Yasa; I G. A. Ketut Giantari; I Putu Gde Sukaatmadja; Ni Wayan Ekawati; I G. A. Dewi Adnyani; I G.N. Jaya Agung Widagda; Putu Laksmita Dewi Rahmayanti; Ketut Subawa (Pusat Riset dan Inovasi Nasional, 2023)
Craft businesses engaged in traditional ikat weaving in Central Semarapura Village, Klungkung Regency, have faced intense competition in the last three years and have also experienced a decline in sales turnover. One way to overcome this condition is to carry out social media promotion. Based on the results of an initial interview with one of the actors in a fairly large traditional ikat weaving craft business in Central Semarapura Village, namely Mrs. Ketut Sriani, information was obtained about the decline in sales turnover and the solution was that they had carried out social media promotion but it was not optimal. This is due to their limitations in using social media. This condition is what encourages this community service activity to be carried out to equip business people in the traditional ikat weaving craft business in Central Semarapura Village, Klungkung Regency, to understand how important it is to promote products digitally, one of which is using social media optimally, using all existing social media platforms, following trends. consumer behavior in searching for information, and about designing the content of promotions. The aim of this community service is to equip traditional ikat craft business actors about the importance of social media promotion, getting to know the various existing social media platforms, designing promotional content on social media, as well as assisting in the creation of social media in a comprehensive manner including creating Facebook, Instagram, Line, Tik Tok, WhatsApp, in order to increase promotional capabilities and sales turnover.